PENGARUH CURRENT RATIO DAN DEBT TO EQUITY RATIO TERHADAP RETURN ON EQUITY PADA PT. WASKITA KARYA (PERSERO) TBK PERIODE 2013 - 2022 - Nazillah, Avriyani; Supriatna, Agus (Journal of Research and Publication Innovation, 2024)
This study aims to determine whether there is a significant effect between Current Ratio and Debt to Equity Ratio on Return on Equity at PT.Waskita Karya (Persero) Tbk. The method used in this study is a quantitative method by taking data from the financial statements of PT. Waskita Karya (Persero) Tbk for the period 2013-2022. Data analysis used descriptive statistical analysis, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of this research partially show that the Current Ratio variable has a significant effect on Return on Equity, and the Debt to Equity Ratio variable has a significant effect on Return on Equity. Simultaneously the Current Ratio and Debt to Equity Ratio on Return on Equity have an influence, Where Fcount is 11,956 while Ftable is 4.46 and significance is 0.006 <0.05. Based on the Coefficient of Determination Test, the results show 0.774 or a percentage of 77.4%. This shows that the influence of the Current Ratio and Debt to Equity Ratio on Return on Equity is 77.4%, which means that the influence of these two ratios is quite large and around 22.6% is influenced by other variables not examined in this research.